Measuring Students' Engagement in Active Learning on Moodle LMS - Jamaluddin J.E. (Institute of Electrical and Electronics Engineers Inc., 2024)
With the recent COVID-19 pandemic crisis, the Moodle learning management system (LMS) has never been more helpful in classroom management and expanded further to create a more engaging learning space for students worldwide. This study explores and investigates BRIGHTEN, as Universiti Tenaga Nasional (UNITEN) learning management system for the learning process during and towards the endemic. The students' engagement in active learning was evaluated and measured using the course page activity types of analysis available for two consecutive semesters. The activity types investigated were course slides, teaching and learning activities, and assessments. The study focused on the students' views of the course page material as well as the format and structure of the course page. The results of this study indicated that the students were engaged more with the assessments, followed by the course slides and how the learning activities supported the students' interactive nature. Moreover, the course page structure is encouraged to be designed to incorporate both synchronous and asynchronous learning materials to build balance in any course page contents. 2023 IEEE.